Congenitally corrected transposition: complex anatomic repair or Fontan pathway?. (July 2017) - Marathe, Supreet P; Jones, Matthew I; Ayer, Julian; Sun, Jessica; Orr, Yishay; Verrall, Charlotte; Nicholson, Ian A; Chard, Richard B; Sholler, Gary F; Winlaw, David S
Background: Successful anatomic repair of congenitally corrected transposition of the great arteries achieves excellent outcomes. Several centers report excellent long-term survival with the Fontan pathway as well. We have selectively applied both approaches depending on individual patient morphology, with anatomic repair preferred but utilizing the Fontan pathway when high technical complexity or operative risk is anticipated. Methods: Hospital records over an 18-year period (1998–2016) were reviewed to identify patients with congenitally corrected transposition of the great arteries who underwent surgical management. Physiological repairs and hypoplastic ventricles were excluded. Patient- and procedure-related variables were reviewed. Results: We identified 19 patients. Group 1 consisted of 12 anatomic repairs, of which 10 (83.3%) required prior interim staging procedures. Mean age at anatomic repair was 2.6 ± 1.3 years, mean follow-up was 8.7 ± 5.3 years. Nine (75%) patients experienced important complications and 4 (33.3%) required reintervention during follow-up. There were no deaths; one patient required heart transplantation. Group 2 (7 patients) underwent Fontan palliation. Mean age at Fontan completion was 7.2 ± 3.8 years, mean follow-up was 6.3 ± 4 years. There was no reintervention, death, or transplant. Conclusion: Patients with congenitally corrected transposition of the great arteries and two adequate-sized ventricles do well with both anatomic repair and the Fontan pathway in the medium term. Excellent outcomes with reduced early complication and reintervention rates can be achieved for this cohort of patients when a strategy of avoiding complex anatomic repair in favor of the Fontan pathway is used.